The National Cancer Database: Survival Between Head and Neck Melanoma and Melanoma of Other Regions. (26th October 2021) - Cabrera, Claudia I.; Li, Shawn; Conic, Rosalynn; Gastman, Brian R.
Abstract : Objective: Primary site is considered an important prognostic factor for cutaneous malignant melanoma (CMM); however, opinions vary regarding its influence on survival. This study compares overall survival between head and neck melanoma (HNM) and melanoma of other regions (MOR), as well as between melanoma of the scalp and neck (MSN) and melanoma of other head regions (MOHR). Study Design: Level III retrospective cohort study. Setting: Patients from Commission on Cancer–accredited cancer programs affiliated to the National Cancer Database (NCDB). Methods: Patients with HNM (MSN and MOHR included) and MOR, stages I to IV (n = 39, 754), and their linked survival data using the NCDB were identified. Survival was analyzed using propensity score matching methods. Results: After matching using propensity scores, allowing this observational study to mimic a randomized controlled trial, subjects with HNM showed a 22% increased mortality when compared to MOR ( P <. 01). Among those with HNM, hazard was not proportional over time. Overall, subjects with MSN in the first 3.5 years of follow‐up (75% of subjects) showed a 15% increased mortality when compared to MOHR ( P <. 01); however, after 3.5 years, no difference in survival was noted ( P =. 5). Conclusion: Patients with HNM showed a higher mortality when compared to MOR. The risk of death of primary sites within the head and neck varies over time, showing a higher risk of mortality for scalp and neck during the first 3.5 years of follow‐up. This increased risk was not evident after the 3.5‐year threshold. Further research is needed to evaluate additional patient factors or differences in treatment approaches.